On the estimation of survival time and contributory risk factors in the elderly participants in the Tehran lipid and glucose study. A 10-year follow-up - Shakeri, Nezhat; Eskandari, Fatemeh; Hajsheikholeslami, Farhad; Ghanbarian, Arash; Azizi, Fereidoun (Archives of Advances in Biosciences, 2011)
ABSTRACT In the increasing population of the elderly in Iran, so far no prospective health studies have been undertaken. This study was conducted to identify the risk factors of survival time of the elderly of ages above 60 years. Material and Methods: Individuals above 60 years old were recruited in the primary phase of the Tehran Lipid and Glucose Study (TLGS) during 1998-2001. They were followed up for 10 years and their vital status were registered (1998-2008). Age and sex mortality rates for age groups (60-69, 70-79, 80+) were calculated and by using Cox proportional hazard model the hazard rates were estimated. Results: Out of 929 males, 154 (17%) and out of 869 women 85(10%) died during the follow-up years. Cox model showed that diabetes on an average reduces 4.4 years and 2.5 years and smoking reduces 5 and 6.6 years of males' and females' survival time, respectively. BMI>33Kg/m2 and dis-lipoproteinemia reduce 4.5 years and 4 years of women's life span. Tehranian native men on an average live 3 years shorter than other male residents. In addition, hypertension and history of MI, stroke or sudden death of father, brother or son reduce 3.3 years and 4.1 years of men's life time. Conclusion: The elderly population is in need of a healthy ageing to be gained from prevention and intervention. Identification of life time reducing risk factors of elderly helps the policymakers to develop some protocols to increase the life span of the population.